Optimizing Technical Entrepreneurship: Instrument Development for Assessing Technopreneurial Behavior Among Vocational High School Fashion Design Students - Imami Rahayu; Ekohariadi Ekohariadi; Ratna Suhartini (Faculty of Teacher Training and Education Muhammadiyah University of Makassar, 2024)
Objective: Technopreneur behavior refers to the traits, attitudes, and actions of an individual or group involved in technology-based entrepreneurship. Technopreneur is a combination of the word’s